Serum Carotenoid Concentrations Are Weakly Associated with Reported Fatty Acid Intake in U.S. Adults (P02-002-19). (13th June 2019) - Crusan, Ambria; Reicks, Marla; Raatz, Susan
Abstract: Objectives: Dietary carotenoids β-carotene (BCAR), lutein (LUT), and lycopene (LYC) are sourced from fruits and vegetables. The bioavailability of carotenoids is dependent on multiple post-digestion factors, especially the presence of fat in the diet. However, there is a gap in knowledge about whether specific fatty acid classes affect serum carotenoid concentrations. Our primary objective was to assess the association between carotenoid concentrations and reported intake of specific fatty acid classes, utilizing data from What We Eat in America (WWEIA)/National Health and Nutrition Examination Surveys (NHANES). Methods: Data from 9182 male and female participants 20–85 years of age in the NHANES 2003–2006 nationally representative, cross-sectional survey were analyzed to determine the relationships between BCAR, LUT, and LYC concentrations and reported saturated (SFA), monounsaturated (MUFA), and polyunsaturated (PUFA) fatty acid intakes. Due to skewing, we log transformed BCAR. Multiple linear regression estimated the association between carotenoid concentrations and reported fatty acid intakes adjusted for age, sex, and ethnicity. Results: Mean and SE were 2.5 ± 0.9 µg/dL for BCAR, 16.2 ± 8.7 µg/dL for LUT, and 21.8 ± 11.0 µg/dL for LYC. Mean and SE were 26.7 ± 16.9 g for SFA, 30.4 ± 18.4 g for MUFA, and 17.2 ± 11.6 g for PUFA. Significant associations were observed among BCAR concentrations and SFA ( r = −0.15, P < 0.001) and MUFA ( r = −0.14, P < 0.001), LUT and SFA ( r = −0.06, P < 0.001) and LYC and MUFA ( r = 0.16, P < 0.001), SFA ( r = 0.15, P < 0.001) and PUFA ( r = 0.10, P < 0.001). LYC was increased by 10.0 μg/dL for each standard deviation increase in total reported grams of fat. There was no association between reported total fat intakes and BCAR or LUT. Conclusions: Inverse associations between BCAR and LUT and specific fatty acid classes suggests there may be multiple post-digestion factors affecting serum carotenoid concentrations. Serum LYC, unlike other carotenoid concentrations, was positively associated with all fatty acid classes and reported total fat intakes, suggesting importance of fat in absorption. Total fat intake was not associated with BCAR and LUT likely due to adequate carotenoid absorption even at lowest levels of reported fat consumption Funding Sources: N/A.